Engaged scholarship at the South African College of Music of the University of Cape Town: An exploratory study of the perceptions and practices of full-time music academic staff - Davids, John W R (Department of Sociology, 2020)
Debates concerning the concept of 'engaged scholarship’ (ES) in terms of university-society connectivity have become part of the discourse within the shifting South African higher education landscape after 1994. Given the legacy of historical inequalities continuing to permeate all spheres of South African society including higher education, the idea of social-justice-centred engaged scholarship forms the main thrust of the narrative in this thesis. Furthermore, with music inherently geared towards societal engagement, and 'engaged scholarship’ included in UCT’s latest Social Responsiveness Policy Framework, this thesis critically examines the ES responses - in terms of their perceptions and practices - of music academics at the SACM in post-1994 South Africa. The opening chapter outlines the largely two-pronged research methodology approach pertaining to the analysis and findings of: (1) literature and documents, and (2) in-depth interviews of a representative sample of full-time SACM music academics. Chapter 2 provides a historical sociology unpacking the ES concept as part of an emergent University Third Mission. With developments largely unfolding at American universities, the first part of Chapter 2 shows the development of ES as essentially following two routes. Firstly the Triple Helix notion of university-industry-government (U-I-G) relations since the mid-20th century, identified by Etzkowitz as a 'Second Academic Transformation’ grafted on an earlier 19th century 'First Academic Transformation’ which began in Germany. Then secondly, in the 1990s a broadened view of scholarship aimed at making universities more relevant to the needs of society (i.e. via U-CS or university-civil society links) proposed by Boyer. With the issue of an emergent University Third Mission also entering the South African higher education discourse after 1994, the second part of Chapter 2 highlights conceptual confusion by considering policy and conference debates on 'community engagement’ (CE), the preferred expression for university-society relations in South Africa. Unfolding developments at UCT however have resulted in a discourse of ES becoming integral to this university’s Social Responsiveness Policy Framework after 2012. Moreover with social justice largely absent from CE discourse and the Triple Helix, Cooper has proposed a Quadruple Helix whereby civil society is added as fourth helix (i.e. resulting in U-I-G-CS). The approach of this study, therefore, explores the concept of a social-justice-centred engagement (outlined in part three of Chapter 2) with which it strongly resonates. Chapter 3 focuses attention on the milieu and ethos of UCT and the SACM, putting SACM music academics, part of an elite historically 'white’ university, in perspective. This highlights the entrenched hegemony of the historically 'white’ European settler institutional culture and 'orphan’ status of music indigenous to Africa at the SACM. Against this backdrop Chapter 4 provides a snapshot of the ES perceptions and practices of SACM music academics derived from the in-depth interviews. Importantly, with music largely absent from ES discourse, including at UCT, the critical analysis of the narratives of music academics form the basis for this thesis creating four music-specific ES categories in this chapter, and a proposed typology of music-specific ES in Chapter 5. In addition, a particularly important finding in Chapter 5 depicts the SACM as probably the most engaged UCT department, mainly displaying elements of the Quadruple Helix (U-I-G-CS), but with this engagement significantly skewed towards largely 'white’ civil society. Moreover, given the historically Eurocentric ethos of the SACM, western classical music has retained its uncontested hegemony (including within the SACM student curriculum) despite the introduction in the 1980s of new streams of non-western classical music, including music indigenous to Africa. With reference to ES, the engagement of the majority of SACM music academics was, furthermore, found overwhelmingly to be with the elite social classes. However, 'black’ academics were significantly more engaged with the 'black’ working class than their 'white’ counterparts. Considering the core findings above, pathways enabling the development of more balanced SACM-society relationships, particularly with the 'black’ working class majority have been proposed in the concluding chapter. A crucial recommendation is the decolonisation of the institutional culture and curriculum of the SACM, thereby restoring the former 'Other’, to 'Self’. These being spaces outside the comfort-zone of most music academics, it is suggested that music-specific ES research, potentially able to shift embedded reasoning, should become integral to the decolonisation process.